Underwater Image Processing: State of the Art of Restoration and Image Enhancement Methods. (21st April 2010) - Schettini Schettini, Raimondo Raimondo; Corchs Corchs, Silvia Silvia
Abstract : The underwater image processing area has received considerable attention within the last decades, showing important achievements. In this paper we review some of the most recent methods that have been specifically developed for the underwater environment. These techniques are capable of extending the range of underwater imaging, improving image contrast and resolution. After considering the basic physics of the light propagation in the water medium, we focus on the different algorithms available in the literature. The conditions for which each of them have been originally developed are highlighted as well as the quality assessment methods used to evaluate their performance.